Changes of peripheral blood under the influence of the electromagnetic radiation - Kocharniy V.V. (Морфологія, 2008)
There are a lot of unsolved problems about the influence of electromagnetic radiation on different organs and systems, and also the study of influence of this factor on the biological environments of organism is actual. We have studied the influence of electromagnetic radiation on peripheral blood of normal and pregnant rats. The purpose was to study the changes of peripheral blood cells of normal and pregnant under the influence of electromagnetic radiation. 10 Vistar female rats of 4-6 month age, mass 180-250 g were used. Animals were distributed on 3 groups. The first group is the control, second - pregnant females which did not get the sessions of electromagnetic radiation, third - pregnant females which got the sessions of electromagnetic radiation. The sessions were made by the apparatus «Ramed-expert 02» with frequency 42,3 GHertz, exposition 30 min. daily, on the region of stomach and pelvis during 10 days. In a control group peripheral blood cells did not change substantially. The increase of stab and segmented neutrophils, and insignificant reduction in lymphocyte number in pregnant rats were observed. In pregnant animals which got the sessions of electromagnetic radiation, all indexes remained near the norm.